2019
DOI: 10.1016/j.clinph.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early motor involvement in diabetic polyneuropathy using a novel MUNE method – MScanFit MUNE

Abstract: Highlights MScanFit MUNE yields detailed information on motor unit loss. Motor involvement in diabetic neuropathy may be present as early as sensory involvement. MScanFit MUNE provides sensitive detection of motor involvement in diabetic polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…The changes in axonal function demonstrated in this model were evident without accompanying deficits in nerve conduction values. This finding is in keeping with several clinical studies that have demonstrated that changes in motor nerve excitability occur prior to overt PN [18,[36][37][38]. Increased sensory nerve superexcitability has been demonstrated in human prediabetes, which correlated with glycated hemoglobin in the absence of changes in other nerve excitability parameters and NCV measures suggesting that such isolated findings in one parameter has physiological meaning [39].…”
Section: Discussionsupporting
confidence: 89%
“…The changes in axonal function demonstrated in this model were evident without accompanying deficits in nerve conduction values. This finding is in keeping with several clinical studies that have demonstrated that changes in motor nerve excitability occur prior to overt PN [18,[36][37][38]. Increased sensory nerve superexcitability has been demonstrated in human prediabetes, which correlated with glycated hemoglobin in the absence of changes in other nerve excitability parameters and NCV measures suggesting that such isolated findings in one parameter has physiological meaning [39].…”
Section: Discussionsupporting
confidence: 89%
“…Several techniques are available to classify and characterize peripheral neuropathy. These include clinical assessment and structural and electrophysiology tests such as skin biopsy for intraepidermal nerve fiber density calculation, 22 corneal confocal microscopy (CCM), 23 nerve conduction studies (NCS), 4,24 and the newer MScanfit motor unit number estimation (MUNE) method 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…These include clinical assessment and structural and electrophysiology tests such as skin biopsy for intraepidermal nerve fiber density calculation, 22 corneal confocal microscopy (CCM), 23 nerve conduction studies (NCS), 4,24 and the newer MScanfit motor unit number estimation (MUNE) method. 25,26 There is a need for a detailed assessment of large and small nerve fiber function as well as a quantification of motor function after chemotherapy. 17 We therefore conducted a deep-profile study of patients 5 years after receiving chemotherapy with docetaxel or oxaliplatin using a wide scale of assessment tools to determine the pattern of their neuropathy and neuropathic pain and the effect of quality of life and psychological functioning.…”
mentioning
confidence: 99%
“…CMAP scan MUNE has been tested in several previous studies in both healthy control subjects and individuals with neuromuscular diseases (such as amyotrophic lateral sclerosis), and has shown excellent intra-and inter-rater reproducibility [35]- [39]. In the present study, the same CMAP scan protocol (stimulus steps, duration, frequency, etc.)…”
Section: Resultsmentioning
confidence: 85%